The function of the music of poetry in “the Story of Sheikh San’an” from Manṭiq-uṭ-Ṭayr - Javad Mohaghegh Neyshabouri; Hosein Yazdani; Ali Pedram mirzaei; Fateme Kouppa (مطالعات زبانی و بلاغی)
There will be always a connection between artistic creativity in a poem on one hand and the meanings and concepts conceived by the poet on the other hand, created either consciously or unconsciously. Viewing versed texts from a poetics standpoint will help us discover this connection and may deepen our understanding and pleasure from the text. This treatise seeks to clarify the various dimensions of the music of poetry in the long story of Sheikh San'an, and shows the existence of a connection between musical manifestations and what the poet intends to reveal to us. At the beginning the aesthetic capabilities of the four types of music discernible in poetry (external, internal, lateral and spiritual) which can affect and change the tone of speech, are studied and taken into account. Then manifestation of each type is detected and analyzed in the story of Sheikh San’an. From this study we can arrive at the following conclusions: Firstly, the connection between music of poetry and its meaning and content is much more significant than what may be expected when texts are skimmed. Secondly, there are some capabilities in those four musical element of poetry that make contribution to meaning, which are not much considered and  are not studied yet. This research has shown how changing the semantic position in different parts of Sheikh San'an's story has caused musical changes in each section and how through a  fixed meter of prosody, musical adjustments have come to the aid of meaning.